2010
DOI: 10.1038/emboj.2010.113
|View full text |Cite
|
Sign up to set email alerts
|

TCR-mediated ThPOK induction promotes development of mature (CD24−) γδ thymocytes

Abstract: T lymphocytes develop into two major lineages characterized by expression of the ab and cd T cell receptor (TCR) heterodimers. Within each major lineage, further specialization occurs, resulting in distinct subsets that differ in TCR specificity, phenotype and functional attributes. Thus, in the murine thymus, two distinct subsets of mature (CD24À) cd cells have been identified, that is NK1.1 þ cells, which are enriched for Vc1.1 usage and selectively produce IFNc on stimulation, and CCR6 þ cells, which are en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 45 publications
0
41
1
Order By: Relevance
“…Because strong TCR signals have been thought to be involved in helper lineage choice (13) and ThPOK expression (14), differences in TCR affinity to self-peptide would affect the initial amount of ThPOK protein and thereby be involved in cell fate discrimination in Thpok DTE/DTE mice. It was therefore important to test whether redirected differentiation occurs when all thymocytes expressed the identical TCR.…”
Section: -Bpmentioning
confidence: 99%
“…Because strong TCR signals have been thought to be involved in helper lineage choice (13) and ThPOK expression (14), differences in TCR affinity to self-peptide would affect the initial amount of ThPOK protein and thereby be involved in cell fate discrimination in Thpok DTE/DTE mice. It was therefore important to test whether redirected differentiation occurs when all thymocytes expressed the identical TCR.…”
Section: -Bpmentioning
confidence: 99%
“…76 Th-POK is required for the normal maturation of invariant NKT cells 17,77 as well as for the optimal development of γδ T cells. 78 PLZF is also essential for the development of a variety of innate T cells, including effector NKT cells [79][80][81] and innate γδ T cells. [82][83][84] The effect of PLZF on innate γδ T cell development is not an intrinsic one, however, and instead requires the secretion of IL-4 by PLZF + NKT cells.…”
mentioning
confidence: 99%
“…In the context of conventional T-cell development, we previously provided the first evidence to our knowledge that ThPOK acts as a master regulator of the CD4/CD8 decision point, whose presence or absence dictates development to the CD4 or CD8 lineages, respectively (2, 4). Later we found that ThPOK also plays a widespread and critical role in development of nonconventional T-cell subsets like iNKT cells and selected γδ T-cell subsets (6,39,40). In all of these mature T-cell lineages, ThPOK is expressed at more-or-less high levels under normal physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Alternate commitment to either the CD4 or CD8 lineages is controlled by the Zn finger transcription factor T-helper-inducing POZ/Krueppel-like factor (ThPOK), whose expression is necessary and sufficient to direct development to the CD4 lineage (1)(2)(3)(4). Strong antibody-mediated stimulation can induce ThPOK in developing thymocytes, indicating that ThPOK expression is controlled by TCR signaling (5,6). A loss-of-function mutation of ThPOK does not affect the efficiency of positive or negative selection (4).…”
mentioning
confidence: 99%